2013
DOI: 10.1016/j.chiabu.2012.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Pathways linking childhood maltreatment and adult physical health

Abstract: Objectives This study examined whether a self-reported history of childhood maltreatment (physical, emotional, and sexual abuse and physical and emotional neglect) is related to poor adult physical health through health risk behaviors (obesity, substance dependence, and smoking), adverse life events, and psychological distress. Methods Two hundred and seventy nine (279) women aged 31–54, primarily poor, urban, and African American with a history of substance use during pregnancy, were assessed for perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 64 publications
(100 reference statements)
3
54
0
3
Order By: Relevance
“…4 6 41 A recent study showed associations between childhood trauma (including being physically abused) and increased inflammatory genetic transcription later in life41 as embodying traumatic experiences. Our findings also concur with Min et al 8 that partner and family violence are related to greater likelihood of chronic conditions later in life. It has been suggested that childhood violence may have long-standing effects on older adults' mental health,4 and we further showed that violence across the life course can influence mobility through mental health.…”
Section: Discussionsupporting
confidence: 93%
“…4 6 41 A recent study showed associations between childhood trauma (including being physically abused) and increased inflammatory genetic transcription later in life41 as embodying traumatic experiences. Our findings also concur with Min et al 8 that partner and family violence are related to greater likelihood of chronic conditions later in life. It has been suggested that childhood violence may have long-standing effects on older adults' mental health,4 and we further showed that violence across the life course can influence mobility through mental health.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with prior literature (Alegria et al, 2013;Min et al, 2013), confounding variables controlled for in the analyses included gender, age, race, education, personal income, marital status, and reported experience of adulthood adverse events. Both regressions were a threestep analysis.…”
Section: Hierarchical Linear Regressionsmentioning
confidence: 56%
“…For example, childhood adverse events pose an increased risk of several physical health conditions in adulthood (Afifi, Mota, MacMillan, & Sareen, 2013;Felitti et al, 1998;Min, Minnes, Kim, & Singer, 2013;Morton, Schafer, & Ferraro, 2012;Rapoza et al, 2014;Scott et al, 2011). Scott and col leagues (2011) found that individuals who reported at least three childhood adverse events experienced an increased risk of heart disease, asthma, diabetes, osteoarthritis, chronic spinal pain, and frequent or severe headaches.…”
Section: T He Child Abuse Prevention and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to those studies that have been undertaken, childhood maltreatment of all forms have been associated with depression, suicide attempts, alcohol misuse and psycho-active substance misuse (Dube et al 2003;Chapman et al 2004;Min et al 2007;Wu et al 2010;Min et al 2013). Furthermore, increasing numbers of traumatic experiences (including parental separation, mental illness in the household and criminal household members in addition to childhood abuse or neglect) have been associated with poorer levels of psychosocial functioning (Wu et al 2010) and greater levels of psychological distress and recurrent depressive disorder (RDD; Chapman et al 2004).…”
Section: Introductionmentioning
confidence: 97%